638. SAFETY AND EFFICACY OF REPEATED TALAPORFIN SODIUM PHOTODYNAMIC THERAPY (PDT) FOR ESOPHAGEAL CANCER. (24th September 2022) - Tamaoki, Masashi; Yokoyama, Akira; MItani, Yosuke; Horimatsu, Takahiro; Ohashi, Shinya; Katada, Chikatoshi; Muto, Manabu
Abstract: While Talaporfin sodium photodynamic therapy (PDT) is an effective and safety salvage treatment for local failure after chemoradiotherapy for esophageal cancer, some case developed local failure. For such case, repeated PDT could be indicated. However, safety and efficacy of repeated PDT as a salvage treatment for esophageal cancer has not been elucidated. We retrospectively reviewed 60 patients with esophageal cancer who were treated with salvage PDT at Kyoto University Hospital between October 2015 and August 2021. Among 60 patients, repeated PDT after the first PDT was indicated for 21 lesions in 16 patients (26.7%), of which eight lesions were residual tumor, four were local recurrence after complete response (CR) after the first PDT at the primary site, and nine were metachronous lesion. The total session of repeated PDT was 33; 20 were for primary sites and 13 were for metachronous sites. Among them, seven patients (43.8%) achieved local (L) -CR and 13 lesions (61.9%) achieved lesion L-CR. By session, 14 sessions (42.4%) achieved L-CR. There were no severe adverse events except for one patient of perforation. Repeated PDT could be an effective and safe treatment option for local failure after salvage PDT for esophageal cancer.